A comparison of hip fracture incidence rates among elderly in Sweden by latitude and sunlight exposure. Issue 2 (March 2014) - Nilson, Finn; Moniruzzaman, Syed; Andersson, Ragnar
Background: Research has shown that hip fracture risk increases with latitude; hypothetically due to reduced sunlight exposure and its effect on bone quality. Sweden, with large differences in latitude and UV radiation, is ideal to study in order to analyse the association between latitude and UV radiation on age- and sex-specific hip fracture rates among elderly. Method : Aggregated (2006–2008) age- and sex-specific hip fracture data was obtained for each Swedish municipality as well as the municipality's latitudinal coordinates and aggregated (2006–2008) UV radiation levels. Pearson correlations were calculated between hip fracture incidence rates, latitude and UV radiation. Independent t tests were calculated on tertile-categorized latitudinal data in order to investigate the difference in hip fracture risk between these categories. Results : Statistically significant correlations were seen in all groups between hip fracture incidence rates and latitude as well as UV radiation. The independent t tests showed that this correlation was mainly due to high incidence rates in high latitude municipalities. Conclusions : Statistically significant correlations are seen between hip fracture incidence rates and latitude as well as UV radiation in Sweden and the northern parts of Sweden have an increased risk of hip fractures compared to the middle and southern parts. To our knowledge this is the first study using a national discharge register that shows this relationship and provides a starting point for further research to investigate why populations in northern Sweden have a higher risk of hip fractures compared to other Swedish regions.